Sustainable Vertical Fire-Tube Boiler Design for Patchouli Distillation - Muhammad Ilham Maulana; Zulfan; RM Fuad; Yusmanizar (Jurnal Inotera, 2026)
Patchouli (Pogostemon cablin Benth) distillation in small-scale industries commonly relies on conventional wood-fired drum boilers that produce unstable steam, consume excessive fuel, and reduce extraction efficiency. This study presents the design of a sustainable vertical fire-tube boiler to improve the thermal performance, operational safety, and energy efficiency of patchouli distillation. The boiler was developed using an engineering design approach involving thermodynamic analysis, structural and dimensional calculations, material selection, pressure-vessel design based on the Boiler and Pressure Vessel Code, and three-dimensional computer-aided modelling. The proposed design operates at 3 bar and 133.5 °C, producing saturated steam at a rate of 0.10 kg s⁻¹. The calculated heat duty is 205.8 kW, requiring an LPG consumption rate of 0.0053 kg s⁻¹. The final design consists of a 1200 mm high and 750 mm diameter vertical boiler equipped with 26 stainless-steel fire tubes, providing an effective heat-transfer area of 1.74 m² while satisfying structural safety requirements. The estimated thermal efficiency of approximately 80% demonstrates a considerable improvement over conventional boilers by reducing fuel consumption and promoting cleaner combustion. Overall, the proposed boiler provides a compact, safe, and energy-efficient steam generation system suitable for sustainable modernization of small-scale patchouli distillation.